2006
DOI: 10.1002/art.21656
|View full text |Cite
|
Sign up to set email alerts
|

Acute occlusive large vessel disease leading to fatal stroke in a patient with systemic lupus erythematosus: Arteritis or atherosclerosis?

Abstract: A woman with a history of systemic lupus erythematosus presented with extensive bilateral strokes due to acute inflammatory, occlusive large vessel disease affecting several aortic branches including the carotid, subclavian, renal, and iliac arteries. We quantitatively characterized the arterial inflammation in this patient and compared it with the inflammatory infiltrates from 22 patients with conventional atherosclerosis. Profound histomorphologic differences from conventional atherosclerosis (predominance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…[3][4][5] However, our patient presented massive cerebellar infarction without any previously supposed mechanisms. [7] However, our patient differed from those patients because she presented with life-threatening cerebellar infarction and vasculitic pathology in a single region. Pathology of the lesion also showed features of vasculitis.…”
Section: Massive Vasculitic Cerebellar Infarction In Patient With Sysmentioning
confidence: 56%
See 1 more Smart Citation
“…[3][4][5] However, our patient presented massive cerebellar infarction without any previously supposed mechanisms. [7] However, our patient differed from those patients because she presented with life-threatening cerebellar infarction and vasculitic pathology in a single region. Pathology of the lesion also showed features of vasculitis.…”
Section: Massive Vasculitic Cerebellar Infarction In Patient With Sysmentioning
confidence: 56%
“…[3] The common causes of cerebral infarction in patients with SLE include cardio-embolism, hypercoagulable states and atherosclerosis. [6,7] These reports describe bilateral multiple cerebral infarcts with necrotizing vasculitis [6] or extensive bilateral cerebral infarction with acute occlusive large-vessel disease. She had serological markers of highly active SLE, high titers of anti-dsDNA and low complement level.…”
Section: Massive Vasculitic Cerebellar Infarction In Patient With Sysmentioning
confidence: 99%
“…Targeting of a CD8 + T cell immune response against arterial smooth muscle cells has been shown to markedly aggravate atherosclerosis in Apoe -/- mice [35]. CD8 + T cells have also been implicated in the accelerated atherosclerosis that occurs in patients with autoimmune diseases such as systemic lupus erythematosus [36]. In a study by Elhage and coworkers [37] CD8 deficiency did not influence atherosclerosis development in Apoe -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that atrial myxoma with metastasis causing inflammation in the vessel wall could be misdiagnosed as Takayasu arteritis (Tan et al, 2010;Fung et al, 2014). Most pathologic lesions in SLE are not caused by vasculitis, but acute occlusion of large arteries due to arteritis (Conen et al, 2006) and focal sites of arteritis affecting the coronary arteries or aorta have been described. Svenungsson et al showed that patients with SLE had increased IMT compared to SLE controls in a study of 26 patients (Svenungsson et al, 2001).…”
Section: Discrepancy Between Clinical Diagnosis and Sonographic Diagnmentioning
confidence: 99%